Peru : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
This paper assesses the performance of Peru's alternative fiscal rules in supporting medium-term fiscal policy objectives. Peru has shown steady fiscal surpluses and declining debt vulnerabilities. Subnational government constrains to borrow internationally have been relaxed, which could become a concern in the future. Current debt levels are already low, which may allow the authorities to move quicker toward a structural balance rule, or even propose a small structural deficit, without jeopardizing debt sustainability.